Corporate Responsibility For Criminal Actions Of Song Copyright Under The 28 Law Of 2014 - Putera, Ade; Sunardi, Sunardi; Arief, Hanafi (International Journal of Law, Environment, and Natural Resources, 2023)
Research entitled "Corporate Responsibility for Crime of Song Copyright According to Law Number 28 of 2014" aims to analyze how copyright crimes are regulated in Indonesian positive law and to analyze corporate responsibility for copyright infringement according to the Copyright Law Number 28 of 2014. This research is normative legal research, which examines laws and regulations in a coherent legal system and unwritten legal values ??that live in society, which are related to corporate responsibility for copyright infringement according to the law 28 of 2014. The results of the study stated that copyright crimes, including song copyrights, are regulated in the Copyright Act as part of Indonesian positive law. Article 112 of the Copyright Law Number 28 of 2014 states that everyone who without rights commits the acts referred to in Article 7 paragraph (3) and/or Article 52 for commercial use, shall be punished with imprisonment for a maximum of 2 (two) years and/or a maximum fine of 300,000,000.00 (three hundred million rupiah). Because legal entities are equated with people, legal entities that commit criminal copyright infringements can also be punished under this article as a form of responsibility. Criminal acts by Corporations are regulated in Article 3 of MA RI Regulation 13/2016 which are criminal acts committed by people based on work relationships, or based on other relationships, both individually and jointly acting for and on behalf of Corporations inside and outside Corporate Environment.